History of posttraumatic stress disorder and outcomes after kidney transplantation. Issue 8 (15th February 2019) - Siwakoti, Ashmita; Potukuchi, Praveen K.; Thomas, Fridtjof; Gaipov, Abduzhappar; Talwar, Manish; Balaraman, Vasanthi; Cseprekal, Orsolya; Yazawa, Masahiko; Streja, Elani; Eason, James D.; Kalantar‐Zadeh, Kamyar; Kovesdy, Csaba P.; et al.
Abstract : A history of posttraumatic stress disorder (PTSD), if uncontrolled, represents a contraindication for kidney transplantation. However, no previous large study has assessed the association between pretransplant history of PTSD and posttransplantation outcomes. We examined 4479 US veterans who had undergone transplantation. The diagnosis of history of PTSD was based on a validated algorithm. Measured covariates were used to create a matched cohort (n = 560). Associations between pretransplant PTSD and death with functioning graft, all‐cause death, and graft loss were examined in survival models. Posttransplant medication nonadherence was assessed using proportion of days covered (PDC). From among 4479 veterans, 282 (6.3%) had a history of PTSD. The mean age ± standard deviation (SD) of the cohort at baseline was 61 ± 11 years, 91% were male, and 66% and 28% of patients were white and African American, respectively. Compared to patients without a history of PTSD, patients with a history of PTSD had a similar risk of death with a functioning graft (subhazard ratio [SHR] 0.97, 95% confidence interval [CI] 0.61‐1.54), all‐cause death (1.05, 0.69‐1.58), and graft loss (1.09, 0.53‐2.26). Moreover, there was no difference in immunosuppressive drug PDC in patients with and without a history of PTSD (PDC: 98 ± 4% vs 99 ± 3%, P  = .733 for tacrolimus; PDC: 99 ± 4% vs 98 ± 7%, P  = .369 for mycophenolic acid). A history of PTSD in US veterans with end‐stage renal disease should not on its own preclude a veteran from being considered for transplantation. Abstract : Kidney transplant recipients who are US military veterans with a history of posttraumatic stress disorder show similar medication adherence, survival, and graft loss risk compared to veteran recipients without PTSD.